Sagittal plane joint mechanics during downhill running in female distance runners - Wells, M. D.; Dickin, D. C.; Popp, J.; Wang, H. (Sports Medicine and Health Science, 2025)
Background Hill training is often used as a foundational training method to increase strength and speed. However, there is limited research regarding the mechanics involved in downhill running, particularly for declines greater than -10%, despite trail and hill training commonly occurring in long distance running. Thus, the purpose of this study was to quantify the biomechanics of downhill running at four different declines compared to a level surface in female distance runners and to assess the potential risk of injury relative to level running.